1) x2-x-y2-y
2) x2 -y2 +x-y
3) 3x-3y+x2-y2
4) 5x-5y+x2-y2
5) x2-5x-y2-5y
6) x2-y2 +2x-2y
7) x2 -4y2+x+2y
8) x2-y2-2x-2y
9) x2 -4y2+2x+4y
2x2(x2+y2)+2y2(x2+y2)+5 (y2+x2) với x2+y2=1
2x2(x2+y2)+2y2(x2+y2)+5 (y2+x2) với x2+y2=1
Biết x 2 + y 2 = 1 . Tính giá trị của biểu thức M = 3 x 2 ( x 2 + y 2 ) + 3 y 2 ( x 2 + y 2 ) – 5 ( y 2 + x 2 )
A. -8
B. 2
C. 8
D. -2
Thu gọn đa thức
C= x2-y2+z2-x2+y2-z2+x2+y2+z2
rút gọn P=2/x-(x2/(x2-xy)+(x2-y2)/xy-y2/(y2-xy)):(x2-xy+y2)/(x-y)
r tìm gt P với |2x-1|=1 ; |y+1|=1/2
( x – y ) 2 bằng:
A. x 2 + y 2
B. ( y – x ) 2
C. y 2 – x 2
D. x 2 – y 2
Cho M = x 2 + y 2 + x y x 2 − y 2 : x 3 − y 3 x 2 + y 2 − 2 x y và N = x 2 − y 2 x 2 + y 2 : x 2 − 2 x y + y 2 x 4 − y 4 . Khi x + y = 6, hãy so sánh M và N
A. M < N
B. M > N
C. M ≥ N
D. M = N
-x2 + 2xy - y2 / x+ y = ? / y2 - x2